P8 Raised faecal calprotectin following resection for Crohn's disease is associated with post-operative recurrence. (19th June 2022) - Brownson, Emily; Nicholson, Gary; Macdonald, Jonathan; Seenan, John Paul
Abstract : Introduction: 50% of patients with Crohn's Disease (CD) will have surgery within the first 10 years, with 35% requiring additional surgery. Active inflammation at resection margins and the presence of epithelioid granulomas in resected tissue have been linked to recurrence. Faecal calprotectin (FCP) is a useful tool in the assessment of inflammatory bowel disease, and has been shown to have good negative predictive value for post-operative recurrence. We aimed to define our local post-operative CD population, and to assess associations with post-operative disease recurrence. Methods: CD resections between 2008-2014 were identified from the NHS Greater Glasgow & Clyde Pathology Archive. Demographic data was obtained from Electronic Patient Records. Pathology reports from the index resection specimen were reviewed for presence of epithelioid granulomas and inflammation at the resection margins. A minimum of five years of follow up data was collected. Type of recurrence was recorded as: clinical recurrence - symptom flare requiring course of steroids or inpatient admission; biochemical recurrence - FCP >250µg/l; endoscopic recurrence; or surgical recurrence – the need for further CD-related surgery. Results: 303 patients (59.5% female) were identified. 49 patients (16.1%) required further surgery for Crohn's disease within the five-year follow up period. FCP >250µg/l at one year was associated with surgical recurrence at 5 years (p=.007). This association was not sustained when the cut-off for FCP was lowered to 150 µg/l. The presence of epithelioid granulomas in the index resection specimen was associated with surgical recurrence (p=.005), however the presence of inflammation at the resection margins was not associated with need for further surgery. In the cohort with inflammation at resection margins, FCP >250µg/l was associated with surgical recurrence (p=.02). The same was true in the cohort with epithelioid granulomas in their index resection specimen (p=.01). There was no increase in risk of surgery in the groups without pathological risk factors, even those with raised calprotectin. Conclusions: Our study suggests rates of recurrence post-resection for Crohn's disease in line with published data. Faecal calprotectin >250µg/l one year after resection was associated with increased risk of further surgery within five years in our cohort. Our data suggest that in groups with pathological risk factors for recurrence, raised faecal calprotectin predicted need for surgical intervention. Further multivariate analysis will be required to confirm this relationship.